Extraction of Molasses from Sugar Crystals in a Centrifuge - Please, Colin P.; Fowkes, Neville D.; Mason, David P.; Khalique, Masood M.; Hutchinson, Ashleigh Jane; Rademeyer, Maryke; Loubser, Richard; Davis, Steve (Mathematical Modelling and Analysis, 2014)
Massecuite is a mixture of sugar crystals and molasses produced during the manufacture of sugar. A centrifuge, which is a rotating cylindrical basket, is used to separate the sugar crystals from the molasses. Water and steam are introduced into the centrifuge during the latter part of the process to further facilitate drainage. Models developed indicate that a fifty percent increase in molasses drainage can result from the addition of steam, whereas water does not significantly affect drainage.